(3EOGQI GdYedjGJ GdeUQajI h GdQbGHI YdjgG (B/s - (3GdYjGOj, GMeO UHMjs ((3YeGf(B: s (3OGQ GdacQ(B, s, 2010)
(3eYfi abg GdeYGedGJ h GdGdaGX PGJ GdUdI , fXQI GdGSdGe Gdi abg GdeYGedGJ GdeGdjI , NUGFU abg GdeYGedGJ GdeGdjI ,,CfhGY GdeYGedGJ GdeGdjI , eUGOQ abg GdeYGedGJ GdeGdjI , JYQja GdeUQa GdGSdGej , NUGFU h CSS GdeUGQa GdGSdGejI , ChLg GdGJaGb h GdGaJQGb Hjf GdeUGQa GdGSdGejI h GdeUGQa GdQHhjI , Gdeaghe GdGSdGej ddQHM h VhGHWg, CSHGH GSJMbGb GdQHM h JMOjOg , GdHjY h CbSGeg , HjY GdeQGHMI , GdHjhY GdGSJKeGQjI aj GdeUGQa GdGSdGejI , GdGLGQGJ h GdeTGQcGJ , GdVhGHW GdTQYjI ddGYJeGOGJ h GdJMGUjd GdeSJfOjI , h dUfGOjb h eMGaX GdGSJKeGQ GdGSdGejI , GdYhGFO aj GdUjZ GdeUQajI GdGSdGejI h cjajI GMJSGHgG , JYQja GdeUQa GdeQcRj GdQCSeGdj h CgOGag , fTCJg h JWhQ g, hXGFag h ejRGfjJg h GSJbdGdg , GdebUhO HgjFI GdaJhi h GdfJGHYI GdTQYjI h JTcjdgG , GdGHYGO GdKeGfjI ddQbGHI Ydi GdHfhc(B.s
(3eQGLY U(B.297s
Keywords: (3GdQbGHIs; (3GdeUGQas; (3GdeUQa GdGSdGejs